2014
DOI: 10.1682/jrrd.2014.01.0013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperbaric oxygen on eye tracking abnormalities in males after mild traumatic brain injury

Abstract: Abstract-The effects of hyperbaric oxygen (HBO 2 ) on eye movement abnormalities in 60 military servicemembers with at least one mild traumatic brain injury (mTBI) from combat were examined in a single-center, randomized, double-blind, sham-controlled, prospective study at the Naval Medicine Operational Training Center. During the 10 wk of the study, each subject was delivered a series of 40, once a day, hyperbaric chamber compressions at a pressure of 2.0 atmospheres absolute (ATA). At each session, subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…These studies were selected as best evidence due to their investigation of the effects of HBOT on postconcussion symptoms, as well as their randomized controlled trial design. Cifu et al 6 Cifu et al 7 Cifu et al 8 Boussi-Gross et al 9 Characteristics Wolf et al 5 Cifu et al 6 Cifu et al 7 Cifu et al 8 Boussi-Gross et al 9 ATA for 90 min given once daily for 30 treatments; however, both groups improved more than would be expected at 6 mo after brain injury.…”
Section: Results Of Searchmentioning
confidence: 93%
See 4 more Smart Citations
“…These studies were selected as best evidence due to their investigation of the effects of HBOT on postconcussion symptoms, as well as their randomized controlled trial design. Cifu et al 6 Cifu et al 7 Cifu et al 8 Boussi-Gross et al 9 Characteristics Wolf et al 5 Cifu et al 6 Cifu et al 7 Cifu et al 8 Boussi-Gross et al 9 ATA for 90 min given once daily for 30 treatments; however, both groups improved more than would be expected at 6 mo after brain injury.…”
Section: Results Of Searchmentioning
confidence: 93%
“…Five relevant studies [5][6][7][8][9] were found and analyzed as shown in Table 1 (based on Levels of Evidence, Centre for Evidence Based Medicine, 2009). Wolf et al 5 concluded that there was no effect on postconcussion symptoms after an HBOT treatment (2.4 atmospheres absolute [ATA] breathing 100% oxygen) compared with the sham group (1.3 ATA breathing 21% oxygen).…”
Section: Results Of Searchmentioning
confidence: 99%
See 3 more Smart Citations